PENGARUH BERBAGAI MERK DRIED YEAST (Saccharomyces sp.) DAN pH AWAL FERMENTASI TERHADAP KARAKTERISTIK WINE SALAK - Ida Bagus Wayan Gunam (Jurnal Teknologi & Industri Hasil Pertanian, 2017)
The purpose of this research were to find out the effect of different of dried yeast and initial pH of fermentation on the characteristic of salacca wine, and to determine the appropriate of kind of dried yeast and initial pH of fermentation to produce salacca wine with the best characteristic. This research used Randomized Block Design with factorial pattern. The first factor was the kind of dried yeast brand that consisted of 3 kinds namely Lalvin, Levure and Alcotec. The second factor consisted of 5 levels of initial pH, namely 3.5; 4; 4.5; 5; and 5.5. Each treatment was done 2 times, in order to obtain 30 trial units. The data obtained was analyzed using ANOVA followed by Duncans test. Interactions between treatments had very significant effect on the ethanol content, reduction sugar content, and pH, but had significant effect on acid total content. The best treatment was to use the Alcotec brand dried yeast with a treatment of initial pH as 4, with the following characteristics: ethanol content 12.40%, negative content of methanol, reduction sugar content 5.87%, acid total content 0.20%, pH 3.5 after the fermentation, the color was enough pure yellow, the flavor was strong enough, the taste was strong enough, and rather liked over all acceptance.